Children's attitudes towards inclusion of children with disabilities - Alontaga, Jasper Vincent Q. (Animo Repository, 2010)
Children with disabilities refer to those who have identified disabilities, such as physical, behavioral, cognitive, language, or learning disabilities (Lerner, 2003). The field of special education is moving towards the practice of inclusion, where regular students and those with disabilities are placed in the same general classrooms. One crucial factor in an inclusive setting is the attitude of regular students towards their classmates' with disabilities. According to Triandis (1971), "an attitude is an idea charged with emotion which predisposes a class of actions to a particular class of social situations." The primary goal of the study was to develop a twenty five (25) item scale to measure children's attitudes towards inclusion of children with disabilities. A sixty one (61) item scale was initially developed and pilot tested to one hundred fifty (150) Grade 4-6 students from both public and private elementary schools that practice inclusion of students with disabilities. The table of specification of the scale was composed of three areas following the ABC Model, namely affective response, behavioral intention and cognitive response. Reliability analyses resulted to a scale with a Cronbach's Alpha value of C=0.631 for N=25. Factor analyses led to three factors, namely acceptance (with 12 items loading), interaction (with 8 items loading) and curiosity (with 5 items loading). It is recommended to implement the developed scale as a research instrument in studying children's attitudes towards students' with disabilities. It is also suggested that convergent and predictive validity of the scale be established.